HDAC6 Inhibition Corrects Electrophysiological and Axonal Transport Deficits in a Human Stem Cell‐Based Model of Charcot‐Marie‐Tooth Disease (Type 2D) (Adv. Biology 2/2022). Issue 2 (8th February 2022) - Smith, Alec S.T.; Kim, Jong Hyun; Chun, Changho; Gharai, Ava; Moon, Hyo Won; Kim, Eun Young; Nam, Soo Hyun; Ha, Nina; Song, Ju Young; Chung, Ki Wha; Doo, Hyun Myung; Hesson, Jennifer; et al.
Abstract : Charcot‐Marie‐Tooth Disease Treatment In article 2101308, Smith and co‐workers use multielectrode arrays to characterize the functional deficits arising in human iPSC‐derived spinal neurons bearing Charcot‐Marie‐Tooth disease type 2D‐associated mutations. Loss of activity and network development correlate with reductions in mitochondrial movement, suggesting a defective axonal trafficking mechanism. Observed deficits were ameliorated by treatment with HDAC6 inhibitors, indicating a potential avenue for future therapeutics.